2021
DOI: 10.1080/21655979.2021.1918505
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Diacylglycerol kinase zeta (DGKZ) suppresses tumorigenesis and progression of cervical cancer by facilitating cell apoptosis and cell cycle arrest

Abstract: Diacylglycerol kinase zeta (DGKZ) participates in cancer progression. Here, the current work aims to identify the functional role of DGKZ in cervical cancer (CC). DGKZ expression in cervical cancer tissues and paired adjacent normal cervical tissues was assessed using Immunohistochemistry assay. SiHa and HeLa cells were transfected with lentivirus plasmids (sh-DGKZ or sh-NC) to evaluate the effects of DGKZ knockdown on cell proliferation, apoptosis and cell cycle distribution in vitro. Furthermore, BALB/c nude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Similarly, SRSF2 knockdown partially rescued the AASE events in the DGKZ gene (Fig. 5h ), which is involved in carcinogenesis and immune response 55 , 56 , while knocking down three other upregulated SFs ( SRSF1 , SRSF3 , and HNRNPD ) had no effects (Supplementary Fig. S9d ).…”
Section: Resultsmentioning
confidence: 87%
“…Similarly, SRSF2 knockdown partially rescued the AASE events in the DGKZ gene (Fig. 5h ), which is involved in carcinogenesis and immune response 55 , 56 , while knocking down three other upregulated SFs ( SRSF1 , SRSF3 , and HNRNPD ) had no effects (Supplementary Fig. S9d ).…”
Section: Resultsmentioning
confidence: 87%
“…Then, we further probed whether fluvastatin exerted protective effects on EC progression via knocking down SIRT6 expression. However, the role of PI3K-mTOR pathway in the mechanism of action of fluvastatin related to SIRT6 still requires further study [ 23 , 24 ]. It was obviously found that depletion of SIRT6 triggered more activated cell viability and stimulated the behaviors of EC cells, including proliferation, migration, invasion.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, tumorigenesis is considered to involve disruption of the balance between cell proliferation and apoptosis 31,32 . Dysfunction of programmed cell death enables tumor cells to survive oxidative stress or hypoxia; thus, apoptosis is closely associated with tumor pathogenesis 33 . In this study, we examined the effect of high/low TIGD1 expression on the proliferation of two different OSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%